Bone: The Dragonslayer. - Smith, Jeff, 1960 Feb. 27-; Hamaker, Steve (New York : Graphix, 2006)
The continuing comic book saga finds the Bone cousins face-to-face with a dragon, providing Phoney with a good opportunity to sell beer and Thorn with an unexpected connection to her past; while danger lurks in the form of the rat creature Kingdok.
Horn Book
2.6
3-6
3-6
Keywords: Cartoons and comics; Cousins -- Fiction; Fantasy